Incidence of Postoperative Pain after Single- and Multi-Visit Endodontic Treatment in Teeth with Vital and Non-Vital Pulp - Ince, Bayram; Ercan, Ertugrul; Dalli, Mehmet; Dulgergil, Coruh Turksel; Zorba, Yahya Orcun; Colak, Hakan (European Journal of Dentistry, 2009)
Objectives: To assess the incidence of postoperative pain after single- and multi-visit endodontic treatment of teeth with vital and non-vital pulp.Methods: In total, 306 patients with teeth requiring endodontic treatment were identified and were included in this study. Two experienced clinicians treated the patients, who were randomly assigned to two groups. While the teeth of patients in group 1 were obturated, group 2 were temporarily sealed and obturated after one week. Three days after the root canal instrumentation of each tooth, the patients were asked whether they experienced any postoperative pain and to rate the level of discomfort as no, mild, moderate, or severe pain. Data were analyzed statistically using the chisquare test.Results: No significant difference in postoperative pain was found between vital and non-vital teeth (P>.01). Mild, moderate, and severe pain occurred in 31.4, 13.7, and 4.6% of vital teeth, respectively. Postoperative pain occurred in 107 (69.9%) and 106 (69.3%) teeth in the single- and multi-visit treatment groups, respectively. There was no significant difference in postoperative pain between the two groups (P>.01).Conclusions: The prevalence of postoperative pain did not differ between vital and non-vital teeth. The majority of patients in either groups reported no or only mild pain. (Eur J Dent 2009;3:273-279)
Keywords: Postoperative pain; Endodontic treatment; Non-vital teeth